Methodological and environmental implications for coastal soil identification as support for land management - Gabriel Phelipe Nascimento Rosolem; Yuzi Anaí Zanardo Rosenfeldt; Esdras Coivo Vilella; Daniel Alexandre Heberle; Arcângelo Loss (Revista Brasileira de Ciência do Solo)
ABSTRACT Understanding methodological and environmental implications for coastal soil identification is essential for developing integrated approaches to land management that address soil physical and chemical aspects, environmental dynamics, and their importance for coastal ecosystem sustainability. In this context, a study was conducted in a natural environment, near a marine extraction reserve that was degraded by irregular urbanization and road construction in Santa Catarina Island, Florianópolis, SC, Brazil. The study focused on identifying ecological patterns and impacts associated with acid-sulfate soils. The method used consisted of: i) photointerpretation of physiographic characteristics in a historical series of aerial photos; ii) reinterpretation of historical soil data containing physical and chemical characteristics and available sulfate, and trace elements; and iii) collection, description, and analysis of the soil profile. The main pedogenetic processes affecting the area include sulfidization, paludization, gleization, salinization, and solodization. The soils were classified as Neossolos Quartzarênicos (Typic Sulfaquents and Typic Psammaquents), Gleissolos Tiomórficos (Typic Sulfaquents and Histic-Haplic Sulfaquents), and Gleissolos Háplicos (Sodic Hydraquents). The presence of materials containing reduced inorganic sulfur indicates the need to apply special procedures for the sampling, storage, and analysis of these soils to avoid misleading interpretations and conclusions about soil characteristics. The following recommendations were compiled based on the results: the inclusion of information on procedures for field analysis, sampling, and storage of soil samples in the Manual for Describing and Collecting Soil in the Field; the inclusion of analytical procedures in the Manual of Soil Analysis Methods; revisions to definitions of sulfidic materials, including hypersulfidic and hyposulfidic materials; and the inclusion of these materials as a fifth categorical level in the Brazilian Soil Classification System. Additionally, infrastructure and transport agencies should make alternatives for the total or partial replacement of soft soils in technical standards conditional on the absence of potential acid sulfate soils or on the treatment for mitigating impacts of soil disturbance. This study emphasizes the contribution of soil formation and attributes to mitigating environmental disputes. It also highlights the importance of managing acid-sulfate soils in urban planning to prevent environmental degradation and protect coastal ecosystems.